The Use of Postpartum Hemorrhage Protocols in United States Academic Obstetric Anesthesia Units. Issue 3 (September 2015) - Kacmar, R.M.; Mhyre, J.M.; Scavone, B.M.; Fuller, A.J.; Toledo, P.
<x xml:space="preserve">Abstract</x> (Anesth Analg. 2014;119(4):906–910)